Challenged Public Security by Non-resident Nationals - Tóth, Judit (Magyar Rendészet, 2017)
Hungary as a laboratory may demonstrate the concept on how the nationality law framed by human rights and EU law is using ethnical preferences without textual reference on ethnicity in acquisition. It appears in the amendments of the laws but without impact assessment how the far descendant of ex/nationals living all over the world enjoy preference in acquisition while immigrants residing in Hungary without Hungarian ancestors are treated in a different way. Furthermore, the amendments provide easy acquisition of citizenship and long-term migrant status for non-resident applicants although they are not ethnic Hungarians. There is a common point in these two reverse trends, namely that these facts – together with underestimated procedural and infrastructural needs – are endangering public security. It is proved by the increase of withdrawal for abusive claims and corruption cases relating to the non-resident investors.